2008
DOI: 10.4049/jimmunol.180.5.2815
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Is Involved in LFA-1 Extension Triggered by CXCL12 but Not in a Novel Outside-In LFA-1 Activation Facilitated by CXCL9

Abstract: Chemokines presented on endothelial tissues instantaneously trigger LFA-1-mediated arrest on ICAM-1 via rapid inside-out and outside-in (ligand-driven) LFA-1 activation. The GTPase RhoA was previously implicated in CCL21-triggered LFA-1 affinity triggering in murine T lymphocytes and in LFA-1-dependent adhesion strengthening to ICAM-1 on Peyer’s patch high endothelial venules stabilized over periods of at least 10 s. In this study, we show that a specific RhoA 23/40 effector region is vital for the initial LFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 69 publications
2
23
2
Order By: Relevance
“…By use of blocking peptides, Giagulli et al 15 had found that RhoA is required for leukocyte beta-2 integrin activation in endothelial arrest. These findings were recently confirmed and extended by Pasvolsky et al, 39 who showed that RhoA blocking peptides regulate intermediate affinity epitope expression of LFA-1 in T cells in flow. We now show that cytohesin-1 regulates the GTP loading of RhoA in leukocytes and we consistently report that both cytohesin-1 and RhoA mediate chemokine-induced activation epitope expression of CD18 in dendritic cells (Figure 2, Figure 6E, and data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…By use of blocking peptides, Giagulli et al 15 had found that RhoA is required for leukocyte beta-2 integrin activation in endothelial arrest. These findings were recently confirmed and extended by Pasvolsky et al, 39 who showed that RhoA blocking peptides regulate intermediate affinity epitope expression of LFA-1 in T cells in flow. We now show that cytohesin-1 regulates the GTP loading of RhoA in leukocytes and we consistently report that both cytohesin-1 and RhoA mediate chemokine-induced activation epitope expression of CD18 in dendritic cells (Figure 2, Figure 6E, and data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…This supports the notion that in vivo, the main modification of ␣ L ␤ 2 leading to adhesion is due to a shift from a low to highaffinity conformation. Results in primary human T cells confirm this observation: a permeant peptide blocking the 23-40 region reduces the stable arrest on ICAM1 coating or HEV in vivo [44]. However, no role for the 92-119 region in ␤ 2 stable nor transient adhesion has been reported in primary human T cells.…”
Section: Rhoasupporting
confidence: 57%
“…RhoA has been shown to regulate leukocyte integrin activation in several situations. [47][48][49][50] In thymocytes, RhoA was shown to be required for optimal integrin activation by Rap1, 51 indicating that RhoA can be part of Rap-dependent inside-out activation of integrins. Given that Rap regulates ARAP3 as a Rho GAP and that ARAP3-deficient neutrophils are characterized by heightened ␤2 integrin activity and hyperresponsiveness in adhesion-dependent processes, we speculate that Rap activates ARAP3 as a Rho GAP to fine-tune integrin activity in neutrophils.…”
Section: Arap3 Does Not Modulate Rap Activity But Affects Rhoa In Nementioning
confidence: 99%